Sorption, desorption and leaching potential of sulfonylurea herbicides in Argentinean soils - Azcarate, Mariela Pamela; Montoya, Jorgelina Ceferina; Koskinen, William C. (2018)
The sulfonylurea (SUs) herbicides are used to control broadleaf weeds and some grasses in a variety of crops. They have become popular because of their low application rates, low mammalian toxicity and an outstanding herbicidal activity. Sorption is a major process influencing the fate of pesticides in soil. The objective of this study was to characterize sorption–desorption of four sulfonylurea herbicides: metsulfuron-methyl (methyl 2-[(4-methoxy-6-methyl-1,3,5-triazin-2-yl)carbamoylsulfamoyl)] benzoate), sulfometuron-methyl (methyl 2-[(4,6-dimethylpyrimidin-2-yl)carbamoylsulfamoyl]benzoate), rimsulfuron (1-(4,6- dimethoxypyrimidin-2-yl)-3-(3-ethylsulfonyl-2-pyridylsulfonyl)urea) and nicosulfuron (2-[(4,6-dimethoxypyrimidin-2-yl) carbamoylsulfamoyl]-N,N-dimethylnicotinamide) from different soil horizons of different landscape positions. Sorption was studied in the laboratory by batch equilibration method. Sorption coefficients (Kd-SE) showed that rimsulfuron (Kd-SE D 1.18 to 2.08 L kg -1) and nicosulfuron (Kd-SE D 0.02 to 0.47 L kg -1) were more highly sorbed than metsulfuron-methyl (Kd-SE D 0.00 to 0.05 L kg -1) and sulfometuron-methyl (Kd-SE D 0.00 to 0.05 L kg -1). Sorption coefficients (Kd-SE) were correlated with pH and organic carbon content. All four herbicides exhibited desorption hysteresis where the desorption coefficients (Kd-D) > Kd-SE. To estimate the leaching potential, Koc and ground-water ubiquity score (GUS) were used to calculate the half-life (t1/2) required to be classified as “leacher” or “nonleacher”. According to the results, rimsulfuron and nicosulfuron herbicides would be classified as leachers, but factors such as landscape position, soil depth and the rate of decomposition in surface and subsurface soils could change the classification. In contrast, these factors do not affect classification of sulfometuron-methyl and metsulfuron-methyl; they would rank as leachers.